Plasma leyels of luteinizing and follicle stimulating hormones in naloxone-treated subestrus buffaloes - CHANDRASEKHAR, T; MADAN, M L (The Indian Journal of Animal Sciences, 2013)
To stude the effects of an antiopiate naloxone on hypophysial gonadotrophins; luteinizing hormone (LH) and follicle stimulating hormone (FSH) and estrus behaviour in subestrous buffaloes naloxone hydrochloride (1.5 mg/kg wt) dissolved in saline was infused into the jugular vein continuously for 4 hr through a catheter at a rate of 0.66 ml/min. Similarly, saline was infused 2 days before naloxone treatment. Blood sampling was done at 15 min interval during the infusion period and at hourly interval for 4 hr post-infusion in both the treatments. Mean LH levels measured showed a significant (P